Simulating tripping characteristic of circuit breakers using least square method: article / Natasha Hashim - Hashim, Natasha (Universiti Teknologi MARA (UiTM), 2009)
Fault studies analysis an important part of power system analysis. The magnitude of the fault currents depend on the interval impedance of the intervening circuit. Fault current will be the problem in the network system which is it can damage the equipments. Fault studies are also used to obtain the rating of the protective devices. By using the protective devices, fault current which occurs at all bus will detect in the few second. "Simulating Tripping Characteristics of Circuit Breakers Using Least Square Method" is propose to overcome the fault problem occurred in the electrical network system. This project is to describe the relation of rated fault current and tripping time in different circuit breakers performance. The rated fault current of a circuit breaker is the maximum current a circuit breaker can safely interrupt. The tripping time setting of a circuit breaker relates to the performance of the circuit breaker over a period of time. It defines the ability of the breakers to remain closed for a time interval under high fault current conditions. It is important to understand the performance of the specific devises in order to apply it properly. The analysis of balance fault will develop by MATLAB software version 7.6.